1993
DOI: 10.1006/viro.1993.1298
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genomic Sequence and Phylogenetic Analysis of the Lactate Dehydrogenase-Elevating Virus (LDV)

Abstract: The apparently complete sequence of the RNA genome of the neurovirulent isolate of lactate dehydrogenase-elevating virus (LDV-C) has been determined. The LDV-C genome is at least 14,222 nucleotides in length and contains eight open reading frames (ORFs). ORF 1a, which encodes a protein of 242.8 kDa and is located at the 5' end of the genome, contains at least two putative papain-like cysteine protease domains, and one putative chymotrypsin-like serine protease domain. This ORF terminates with a UAG stop codon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
153
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 0 publications
4
153
0
Order By: Relevance
“…2). Similar variability of the Ph1 amino acids has been described for the leader PCP of arteriviruses and coronaviruses, which have Gly\Gly, Gly\Ala, Gly\Val or Gly\Tyr dipeptides as cleavage sites (Godeny et al, 1993 ;Dong & Baker, 1994 ;den Boon et al, 1995).…”
mentioning
confidence: 52%
“…2). Similar variability of the Ph1 amino acids has been described for the leader PCP of arteriviruses and coronaviruses, which have Gly\Gly, Gly\Ala, Gly\Val or Gly\Tyr dipeptides as cleavage sites (Godeny et al, 1993 ;Dong & Baker, 1994 ;den Boon et al, 1995).…”
mentioning
confidence: 52%
“…NSP2 has been shown to be variable in length among sequenced isolates of arteriviruses (1,36,39,61). PRRSV type 1 strain LV NSP2 is 861 aa in length while type 2 strains have an additional 100 aa or more, and lactate dehydrogenase-elevating virus and EAV encode NSP2 proteins which are 733 and 401 aa in length, respectively (1,20,36,82,85). Snijder et al (66) found that the NSP2 protein of EAV was involved in proteolysis of replicase precursors and membrane association of the virus replication complex, but no confirming work has been reported for other arteriviruses.…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…Subsequently, the CVL group was expanded to include the arteriviruses, which also produce a 3'-coterminal nested set of mRNAs. The protein-coding regions of the genomes of EAV (den Boon et al, 1991 b), LDV (Kuo et al, 1991 ;Godeny et al, 1990Godeny et al, , 1993Chen et al, 1993) and LV (Meulenberg et al, 1993a;Conzelmann et al, 1993) have now been sequenced completely. Although arterivirus replicase genes are considerably smaller (9.5 to 12 kb) than their toro-and coronavirus counterparts, they also contain two ORFs, the downstream ones of which are expressed by ribosomal frameshifting.…”
Section: The 'Coronavirus-like' Replicasementioning
confidence: 99%